The struggle for abolition of use of customary law in volost courts of Russian Empire at turn of the XIX–XX centuries - O. V. Kalyuzhnaya (Омский научный вестник: Серия "Общество. История. Современность")
This article is devoted to the issues of socio-political discussions on the abolition of the application of customary law in the activities of the volost courts of the Russian Empire at the turn of the XIX–XX centuries. In the light of the activities of Advisory bodies that considered and developed draft reforms of legislation on farmers. For the first time, the author shows the features of approaches to the studied problem, identified in the materials of the periodical press and provincial committees of the Special Comission on the needs of the agricultural industry. The result of the research is the identification of three key approaches to the problem of customary law in volost justice, which are formed in the socio-political thought of the period under review